Prophecy in later Islamic thought : the mystical views of Shah Waliyyullah ad-Dihlawi (d. 1176 ah/1762 ce) - Ariff, Syamsuddin (Darussalam University, 2009)

(untitled)
Prophecy is so central and essential a concept to Islam that hardly can we find a Muslim thinker who did not talk or write about it. Philosophers and theologians from al-Jahiz, Abu Hatim al-Razi and Ibn Taymiyyah to Abu al-Hasan al-Nadwi have set out to establish the legitimacy of prophecy and refute the arguments of pagan thinkers who advocated the sufficiency of human reason to arrive at truth and to attain happiness without the aid of prophets or revelation. The issue of prophecy may be examined in several approaches and in terms of the following questions: What exactly is prophecy? Is there such a thing as prophecy? How is prophecy possible? And, why on earth should there be prophets?